(untitled) (Research, Society and Development, 2021)
The scaffolds and their interaction with mesenchymal stem cells are objects of study in bioengineering and tissue repair. Mechanisms such as surface adhesion, proliferation, viability, and cytotoxicity are essential for the development of therapies. The present study analyzed the influence of platelet-rich fibrin (PRF) in viability, cytotoxicity, and proliferation of stem cells from human exfoliated deciduous teeth (SHED) exposed to bovine biomaterial surfaces. The studied groups were divided and analyzed as follows: (S) only SHED as control Group; (SB) SHED + biomaterial; (SBP) SHED + biomaterial + PRF. Analyses of cells seeded in 24-well plates were performed after 24, 48 and 72 hours. Individual groups were subjected to viability, cytotoxicity and cell proliferation tests using neutral red, MTT and crystal violet, respectively; and in the 72-hour group, scanning electron microscopy (SEM) was performed to record cell ultra-morphology. Data were submitted to statistical analysis by two-factor ANOVA with a significance level of 5%. The results demonstrated a better performance in the viability/cytotoxicity and proliferation of stem cells for the group (SBP) in comparison to the group (SB) and the group (S). The applied statistical tests showed that the biomaterial factor, time, and interaction between them gave rise to results with statistical significance. SHED submitted to bovine biomaterial were more viable, proliferative and with lower toxicity when associated with PRF. PRF seemed to activate the metabolism of stem cells in culture, indicating that such an association can bring an effective benefit in clinical outcome.